Comparison of Rectal and Gastrointestinal Core Temperatures During Heat Tolerance Testing - Melissa J. Crowe; Michael T. Meehan; Rhondda E. Jones (Medicina, 2025)
Background and Objectives: Military capability may be reduced in hot environments with individuals at risk of exertional heat stroke (EHS). Heat tolerance testing (HTT) can be used to indicate readiness to return to duty following EHS. HTT traditionally relies on rectal core temperature (Tre) assessment via a rectal probe. This study investigated the use of gastrointestinal core temperature (Tgi) as an alternative to Tre during HTT. A secondary aim was to compare physiological factors between heat-tolerant and heat-intolerant trials. Materials and Methods: Australian Defence Force personnel undergoing HTT following known or suspected heat stroke volunteered (n = 23 cases participating in 26 trials) along with 14 controls with no known heat illness history. Confusion matrices enabled comparison of HTT outcome based on Tgi and Tre. The validity of Tgi compared to Tre during HTT was assessed using correlation and bias. Comparisons between heat-tolerant and intolerant trials were performed using non-parametric tests. Results: Although Tgi correlated closely with Tre (Spearman’s rank correlation <semantics>ρ</semantics> = 0.893; median bias 0.2 °C) there was no consistent pattern in the differences between measures. Importantly, the two measures only agreed on heat tolerance outcome in 80% of trials with Tgi failing to detect heat intolerance identified by Tre in 6 of 8 trials. If Tgi was relied upon for diagnostic outcome, return to duty may occur before full recovery. None of the assessed covariates were related to the difference between Tre and Tgi. In addition, resting heart rate and systolic blood pressure were significantly lower and body surface area to mass ratio significantly higher in heat-tolerant compared to intolerant trials. Conclusions: It is not recommended to rely on Tgi instead of Tre during HTT. Resting heart rate and systolic blood pressure findings point to the importance of aerobic exercise in conveying heat tolerance along with body composition.